Composite solid-state lithium ion battery and preparation method thereof
By using composite solid electrolyte membrane and negative electrode of inorganic framework materials in lithium-ion batteries, combined with materials such as large anions and perfluorobenzene, the expansion and safety problems of the battery at high temperatures are solved, and the cycle life and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202411441456.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-20
AI Technical Summary
Existing lithium-ion batteries have expansion problems at high temperatures, resulting in reduced battery performance and reduced safety. In particular, the expansion of the negative electrode silicon carbon material is difficult to effectively suppress, and the liquid electrolyte is flammable and has the risk of combustion or explosion.
Using composite solid electrolyte membrane and negative electrode containing inorganic framework materials, the dry-in-one manufacturing process is used to form an inorganic support framework network to reduce expansion and deformation, and use materials such as large anions and perfluorobenzene in the electrolyte to improve conductivity and heat Stability, improve battery safety performance.
It significantly suppresses the expansion of the battery at high temperature, improves the cycle life and safety performance of the battery, improves the flame retardant performance and flexibility of the battery, enhances the flat contact of the electrode interface, reduces the deformation of the battery at high temperature, and improves the battery's Overall performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and mainly to a composite solid-state lithium ion battery and a preparation method thereof. Technical Background
[0002] In recent years, the demand for lithium-ion batteries in electronic products, energy storage, and automobiles has continued to increase, and lithium-ion batteries have developed rapidly. At the same time, the requirements for high energy density of batteries have also continued to increase. The increase in energy density will inevitably lead to a decrease in battery high-temperature storage performance and cycle life, as well as a decrease in battery safety. It is necessary to develop a composite solid-state lithium-ion battery that not only improves battery performance but also improves battery safety. Existing liquid lithium-ion battery electrolytes use organic solvents, which are flammable and have poor high-temperature thermal shock resistance. Lithium metal dendrites are easily formed at the negative electrode, piercing the isolation membrane to cause a short circuit between the positive and negative electrodes, resulting in combustion or explosion and other safety issues.
[0003] With the application of silicon negative electrodes, the silicon content in the negative electrodes continues to increase, and the negative electrodes are prone to swelling and deformation, causing battery performance failure, which in turn affects the safety performance of the battery. The current semi-solid and solid electrolytes cannot solve the problem of expansion of negative electrode silicon-carbon materials.
[0004] The inorganic skeleton materials in the composite solid electrolyte membrane and negative electrode sheet ingredients will form an inorganic support skeleton network in the composite solid electrolyte membrane and negative electrode after high temperature. The inorganic skeleton component can significantly inhibit the expansion of the composite solid electrolyte membrane and negative electrode sheet at high temperature, which is conducive to the smooth contact of the electrode interface, especially for the negative electrode silicon-carbon material. Improve the battery cycle life and enhance the battery safety performance.
[0005] On the basis of the polymer solid electrolyte membrane based on PVDF-HFP, a small amount of PMMA is added, which effectively improves the inherent shortcomings of the PVDF-based polymer solid electrolyte itself, such as poor flexibility, easy volatility of the electrolyte, and easy drying of the membrane.
[0006] When making a composite solid electrolyte membrane, a fluorinated sulfonyl imide anion (TFSI-) with a large ionic radius is used in the added liquid electrolyte. Due to the large anionic radius, it is beneficial to charge dispersion and the diffusion coefficient of lithium ions is increased. The composite solid electrolyte of the present invention relies on segment motion to transmit lithium ions, and can effectively suppress the crystallization phenomenon in the solid electrolyte, and promote the transmission of lithium ions in the electrolyte, so as to achieve the improvement of the ionic conductivity of the solid electrolyte at room temperature. Perfluorobenzene (DFB), olefin polyfluorobenzene, etc. are also used in the liquid electrolyte. Perfluorobenzene and olefin polyfluorobenzene are beneficial to the formation of a dense and uniform CEI film at the positive electrode, which can prevent cracks in the particles and the decomposition of the electrolyte membrane, and improve the battery cycle life and safety.
[0007] In the polymer network system, γ-butyrolactone (GBL) in the solvent of the liquid electrolyte acts as a plasticizer, which can make it easier for lithium salts to dissociate Li+, so that Li+ can migrate freely in the solid electrolyte membrane, which also makes this electrolyte have a higher conductivity at room temperature.
[0008] The composite solid electrolyte membrane has relatively high ionic conductivity (greater than 10-4 S cm-1, up to 10-3 S cm-1) and ion migration number, good thermal stability, and good compatibility with electrode materials. Since organic solvents are no longer used in large quantities, it is non-flammable, highly safe, and the negative electrode does not produce lithium dendrites. The electrochemical window is very stable and maintained in the range of 0~5V, and is less affected by the ambient temperature.
[0009] Composite solid-state lithium-ion batteries have complex manufacturing processes, poor charge and discharge rates, and short cycle life. It is necessary to improve them. It is necessary to develop a more suitable composite solid electrolyte, a composite solid electrolyte membrane containing inorganic skeleton support materials and a composite solid-state lithium-ion battery composed of a negative electrode, to improve the battery's electrical performance while also ensuring the battery's safety performance. Summary of the invention
[0010] The purpose of the present invention is to provide a composite solid electrolyte membrane and a composite solid lithium ion battery containing an inorganic skeleton material component to improve the safety performance of the battery. The present invention adopts a solid electrolyte membrane containing an inorganic skeleton material component and a solid negative electrode containing an inorganic skeleton material component. The inorganic skeleton material component can significantly inhibit the expansion of the composite solid electrolyte membrane and the negative electrode sheet at high temperature, which is beneficial to the smooth contact of the electrode interface, especially for negative silicon carbon materials. Improve the battery cycle life and enhance the battery safety performance.
[0011] The present invention provides a method for manufacturing a composite solid electrolyte membrane and a composite solid lithium ion battery containing an inorganic skeleton material component. The positive electrode, electrolyte membrane and negative electrode of the method are all manufactured by a dry all-in-one machine, and the method has the characteristics of simple manufacturing method, low weight of liquid electrolyte used, high safety and prospect of mass production.
[0012] In order to achieve the purpose of the above invention, the following technical solutions are adopted: A composite solid electrolyte membrane and a composite solid lithium ion battery containing inorganic skeleton material components, the composite solid lithium ion battery is mainly divided into three parts: a solid positive electrode, a solid negative electrode containing a skeleton-free material, and a composite solid electrolyte membrane containing an inorganic skeleton material; The solid positive electrode comprises positive electrode active material, conductive carbon, binder, inorganic electrolyte and liquid electrolyte, the above materials are stirred and mixed, heated and pressed into a film by a dry process integrated machine, and composited with the surfaces of both sides of the positive electrode current collector aluminum foil to form a positive electrode; The composite solid electrolyte membrane comprises an inorganic electrolyte, a binder, an inorganic skeleton material, an inorganic material additive and a liquid electrolyte, and the mixture of the above materials is hot-pressed into a composite solid electrolyte membrane by a dry all-in-one machine; The solid negative electrode containing inorganic skeleton material components comprises negative electrode active material, conductive carbon, binder, inorganic electrolyte, liquid electrolyte and inorganic skeleton material. The above materials are stirred and mixed, heated and pressed into a film by a dry all-in-one machine, and then composited with the surfaces of both sides of the current collector copper foil to form the negative electrode.
[0013] Furthermore, the composition ratio of the solid positive electrode is: The total weight of the solid positive electrode is 100%, the positive electrode active material accounts for 80% to 98% of the total weight; the conductive carbon accounts for 0.5% to 3.5% of the total weight; the binder accounts for 0.5% to 4.0% of the total weight; the inorganic electrolyte accounts for 0.5% to 8% of the total weight; the liquid electrolyte accounts for 0.5% to 8% of the total weight; The composition ratio of the composite solid electrolyte membrane containing inorganic skeleton material is: The total weight of the composite solid electrolyte membrane containing inorganic skeleton materials is 100%, wherein the inorganic solid electrolyte accounts for 74% to 95% of the total weight; the binder accounts for 3% to 8% of the total weight; the inorganic skeleton material accounts for 0.5% to 1.5% of the total weight; the additive accounts for 0.5% to 1.5% of the total weight; and the liquid electrolyte accounts for 3% to 10% of the total weight; The composition ratio of the solid negative electrode containing the framework-free material is: The total weight of the solid negative electrode containing the framework-free material is 100%, the negative electrode active material accounts for 85% to 97% of the total weight, the conductive carbon accounts for 0.5% to 1.5% of the total weight; the adhesive accounts for 0.5% to 3.5% of the total weight; the inorganic electrolyte accounts for 0.5% to 5% of the total weight; the liquid electrolyte accounts for 0.5% to 8% of the total weight; and the inorganic framework material accounts for 0.5% to 1.5% of the total weight.
[0014] Furthermore, the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary positive electrode material, a nickel-cobalt-aluminum ternary positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganese oxide positive electrode material, a lithium cobalt oxide positive electrode material, a lithium iron phosphate manganese oxide positive electrode material, a nickel manganese oxide positive electrode material or a lithium-rich manganese-based positive electrode material; the active material of the negative electrode is a composite negative electrode material of silicon carbon or silicon dioxide and artificial graphite.
[0015] Furthermore, the inorganic electrolyte material is at least one of the following materials: lithium germanium phosphosulfide, lithium phosphosulfur halide, lithium aluminum phosphide, lithium aluminum titanium phosphide, lithium lanthanum zirconium oxide, lithium phosphosulfide, and lithium lanthanum zirconium tantalum oxide.
[0016] Furthermore, the binder in the solid positive electrode and / or the solid negative electrode containing the skeleton-free material includes at least one of polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid or polyethylene.
[0017] Furthermore, the inorganic framework material in the composite solid electrolyte membrane containing inorganic framework material and the solid negative electrode containing framework-free material is Li x Na 2-x O•nSiO 2 , where 0≤X≤1, 2≤n≤4.5; As one of the components of the composite solid electrolyte membrane and the solid negative electrode, the inorganic skeleton material is heated and pressed by a dry all-in-one machine during the production of the composite solid electrolyte membrane and the solid negative electrode to form an inorganic support skeleton network in the composite solid electrolyte membrane and the negative electrode.
[0018] Further, the liquid electrolyte comprises an organic solvent, a lithium salt and an electrolyte additive; The organic solvent has the function of dissolving the lithium salt and also has the function of a plasticizer. The organic solvent includes a mixture of two or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, γ-butyrolactone, and N,N-dimethylformamide; Also included are fluorinated solvents such as 2,2,2-trifluoromethylethyl carbonate (MTFEC), 2,2,2-trifluorodiethyl carbonate (ETFEC), and 2,2,2-trifluoroethylpropyl carbonate (PTFEC), or a mixture of more than one thereof; The total weight of the liquid electrolyte is 100%, and the organic solvent accounts for 75% to 85%.
[0019] The lithium salt is mainly lithium bis(trifluoromethylsulfonyl imide), and also includes a mixture of one or more of lithium hexafluorophosphate, lithium perchlorate (LiCIO4), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluorooxalatophosphate, lithium bis(fluorosulfonyl imide), lithium difluorobis(malonate phosphate) and lithium hexafluorophosphate; The total weight of the liquid electrolyte is 100%, and the lithium salt accounts for 8% to 17%; The electrolyte additives also include vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propylene sultone, 1,4-butane sultone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethylene glycol dipropionitrile ether, tris(2,2,2-trifluoroethyl)phosphite, 1,3,6-hexanetrinitrile, citric anhydride, perfluoroglutaric anhydride, fluorobenzene, 2-fluorobiphenyl, boron trifluoride tetrahydrofuran, tris(trimethylsilane) phosphate, cyclic phosphoric anhydride, vinyl sulfate, perfluorobenzene, olefinic polyfluorobenzene, perfluorobenzene, olefinic polyfluorobenzene, one or more thereof; The total weight of the liquid electrolyte is 100%, and the electrolyte additive accounts for 0.5% to 10%.
[0020] Furthermore, the composite solid electrolyte membrane also includes inorganic material additives. The inorganic particles interact with the electrolyte interface and can also provide the electrolyte with higher conductivity. The addition of inorganic fillers can also increase the mechanical strength of the electrolyte and improve the usability of the solid electrolyte membrane. The inorganic material additive includes Al2O3, γ-AlOOH (boehmite), and LiSiO3; The total weight of the solid electrolyte membrane is 100%, and the inorganic material additive accounts for 0.3% to 2%.
[0021] A method for preparing a composite solid electrolyte membrane and a composite solid lithium ion battery containing an inorganic skeleton material component, comprising the following steps: Preparation of solid positive electrode: The solid positive electrode is prepared by uniformly mixing positive electrode active material, conductive carbon, binder and inorganic electrolyte, and then adding liquid electrolyte for thorough mixing to form block particles; the block particles are heated and pressed into a film by a dry all-in-one machine, and then compounded with the surfaces of both sides of the positive electrode current collector aluminum foil to obtain a solid positive electrode.
[0022] Preparation of composite solid electrolyte membrane containing inorganic skeleton material: The composite solid electrolyte membrane is prepared by mixing and stirring an inorganic electrolyte, a binder, and an additive, and then adding an inorganic skeleton material and a liquid electrolyte and mixing them thoroughly to form a block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine to obtain a composite solid electrolyte membrane.
[0023] Preparation of solid negative electrode containing inorganic skeleton material: the solid negative electrode is prepared by mixing and stirring the negative electrode active material, conductive carbon, binder and inorganic electrolyte evenly, then adding inorganic skeleton material and liquid electrolyte to mix them thoroughly to make block granular material; then adding inorganic skeleton material and liquid electrolyte to mix them thoroughly to make block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine, and then compounded with the surfaces of both sides of the negative electrode current collector copper foil to obtain a solid negative electrode of inorganic skeleton material.
[0024] The solid positive electrode, the composite solid electrolyte membrane containing inorganic skeleton materials, and the solid negative electrode containing inorganic skeleton materials are cut, stacked, packaged and hot-pressed in sequence to obtain the composite solid-state lithium-ion battery.
[0025] Compared with the existing technology, the beneficial effects are: (1) Composite solid electrolytes no longer use a large amount of conventional aprotic organic solvents such as EC / PC / EMC / DEC / DMC, which improves the flame retardancy of the solid electrolyte membrane, thereby improving the flame retardancy of the battery and the safety of the battery. The skeleton structure formed by adding inorganic skeleton materials to the composite electrolyte plays a supporting role, reduces expansion and deformation, is conducive to the smooth contact of the electrode interface, and is conducive to improving the performance of the battery.
[0026] (2) The inorganic skeleton material composition can significantly inhibit the expansion of the negative electrode sheet at high temperature, which is conducive to the smooth contact of the electrode interface, and the effect is more obvious for the negative electrode containing high silicon carbon materials. It improves the battery cycle life and enhances the battery safety performance.
[0027] (3) The solid electrolyte membrane of the present invention has relatively high ionic conductivity and good high voltage stability, good flexibility and thermal stability, small deformation at high temperature, and has broad application prospects and practical value. DETAILED DESCRIPTION
[0028] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0029] The invention provides a composite solid electrolyte membrane and a composite solid lithium ion battery containing inorganic skeleton material components.
[0030] The composite solid-state lithium-ion battery includes a solid positive electrode, a solid negative electrode containing a skeleton-free material, and a composite solid electrolyte membrane containing an inorganic skeleton material; wherein the positive and negative solid electrodes include a current collector, and a positive and negative electrode membrane loaded on the surface of the current collector. The solid positive electrode is prepared from a positive electrode active material, conductive carbon, a binder, an inorganic electrolyte and a liquid electrolyte; the composite solid electrolyte membrane is prepared from an inorganic electrolyte, a binder, an inorganic skeleton material, an inorganic material additive and a liquid electrolyte; the negative electrode membrane is prepared from a negative electrode active material, conductive carbon, a binder, an inorganic electrolyte, a liquid electrolyte and an inorganic skeleton material.
[0031] The "binder", "inorganic electrolyte" and "liquid electrolyte" involved in the positive and negative electrode membranes and the composite solid electrolyte membrane; in the present invention, the above three have the same component selection range, but it does not mean that the same "binder", "inorganic electrolyte" or "liquid electrolyte" must be used in the electrode membrane and the semi-solid electrolyte. The component selection in the positive and negative electrode membranes and the composite solid electrolyte is independent of each other.
[0032] As a preferred embodiment, the positive electrode active material includes at least one of a nickel-cobalt-manganese ternary positive electrode material, a nickel-cobalt-aluminum ternary positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganese oxide positive electrode material, a lithium cobalt oxide positive electrode material, a lithium iron phosphate manganese oxide positive electrode material, a nickel manganese oxide positive electrode material or a lithium-rich manganese-based positive electrode material; the active material of the negative electrode is a composite negative electrode material of silicon carbon or silicon dioxide and artificial graphite.
[0033] As a preferred embodiment, the inorganic electrolyte powder material has the following types: lithium germanium phosphosulfide (LiGePS), lithium phosphorus sulfur halide (LiPSX), lithium aluminum phosphide (LiALP), lithium aluminum titanium phosphide (LiALTiP), lithium lanthanum zirconium oxide (LLZO), lithium phosphorus sulfide (LiPS), lithium lanthanum zirconium tantalum oxide (LLZTO) and other inorganic electrolytes. As a more preferred embodiment, the particle size of the inorganic solid electrolyte is 50nm~800nm.
[0034] As a preferred embodiment, the adhesive includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or polyethylene (PE); that is, the adhesive in the solid electrode (positive electrode and / or negative electrode) and the solid electrolyte membrane has the above-mentioned component selection range.
[0035] As a preferred embodiment, the inorganic skeleton material component is characterized in that the inorganic skeleton material in the composite solid electrolyte membrane and the negative electrode sheet ingredients has a molecular formula of Li x Na 2-x O•nSiO 2 [0≤X≤1, 2≤n≤4.5], after being added, it is evenly mixed with other materials, and after preparation, an inorganic support skeleton network is formed in the composite solid electrolyte membrane and the negative electrode.
[0036] As a preferred embodiment, the liquid electrolyte can mainly consist of an organic solvent, a lithium salt and an additive. The organic solvent has the function of dissolving the lithium salt and also has the function of a plasticizer. The organic solvent includes a mixture of two or more of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), γ-butyrolactone, N, N-dimethylformamide (DMF), etc. It also includes a mixture of one or more of the following fluorinated solvents: 2,2,2-trifluoroethyl methyl carbonate (MTFEC), 2,2,2-trifluorodiethyl carbonate (ETFEC), 2,2,2-trifluoroethyl propyl carbonate (PTFEC), etc.
[0037] The lithium salt is mainly lithium bis(trifluoromethylsulfonyl imide), and also includes one or more of lithium hexafluorophosphate, lithium perchlorate (LiCIO4), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluorooxalatophosphate, lithium bis(fluorosulfonyl imide), lithium difluorobis(malonate phosphate), etc. and a mixture of lithium hexafluorophosphate.
[0038] The additives also include vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), 1,3-propylene sultone (PST), 1,4-butane sultone (BS), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFC), ethylene glycol dipropionitrile ether (DENE), tris(2,2,2-trifluoroethyl)phosphite (TTFEP), 1,3,6-hexanetrinitrile (HTCN), citric anhydride, perfluoroglutaric anhydride, fluorobenzene, 2-fluorobiphenyl, boron trifluoride tetrahydrofuran, tris(trimethylsilane) phosphate, cyclic phosphoric anhydride, vinyl sulfate (DTD), perfluorobenzene (DFB), olefinic polyfluorobenzene, etc., one or more of perfluorobenzene, olefinic polyfluorobenzene, etc.
[0039] As a preferred embodiment, the inorganic material additive added to the composite solid electrolyte membrane can provide a higher conductivity of the electrolyte through the interaction between the inorganic particles and the electrolyte interface; the addition of inorganic fillers can also increase the mechanical strength of the electrolyte and improve the usability of the solid electrolyte membrane. The inorganic material includes Al2O3, γ-AlOOH (boehmite), LiSiO3 or other structurally stable metal oxides.
[0040] As a preferred embodiment, the total weight of the solid positive electrode is 100%, the positive electrode active material accounts for 80% to 98% of the total weight; the conductive carbon accounts for 0.5% to 3.5% of the total weight; the binder accounts for 0.5% to 4.0% of the total weight; the inorganic electrolyte accounts for 0.5% to 8% of the total weight; and the liquid electrolyte accounts for 0.5% to 8% of the total weight.
[0041] As a preferred embodiment, the weight proportion of each component in the positive electrode film includes but is not limited to: active material 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 97%, 98%; conductive agent 0.5%, 1.0%, 1.5%, 2%, 2.5%, 3.0%, 3.5%; binder 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4.0%; inorganic electrolyte 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; liquid electrolyte 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%; the above values can use any listed point values, or can use the numerical range formed by any two point values.
[0042] In a further most preferred embodiment, the total weight of the solid positive electrode is 100%, wherein the positive electrode active material accounts for 85% to 97% of the total weight; the conductive carbon accounts for 0.8% to 2.0% of the total weight; the binder accounts for 1% to 3% of the total weight; the inorganic electrolyte accounts for 2% to 7% of the total weight; and the liquid electrolyte accounts for 1% to 6% of the total weight.
[0043] As a preferred embodiment, the composition of the composite solid electrolyte membrane is as follows: the total weight of the composite solid electrolyte membrane is 100%, the inorganic solid electrolyte accounts for 74% to 95% of the total weight; one or more of the binders account for 3% to 8% of the total weight; the inorganic skeleton material accounts for 0.5% to 1.5% of the total weight; the additives account for 0.5% to 1.5% of the total weight; and the liquid electrolyte accounts for 3% to 10% of the total weight.
[0044] As a preferred embodiment, the weight proportion of each component in the composite solid electrolyte membrane includes but is not limited to: inorganic solid electrolyte 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 95%; adhesive 3%, 4%, 5%, 6%, 7%, 8%; inorganic skeleton material 0.5%, 1.0%, 1.5%; additives 0.5%, 1.0%, 1.5%; liquid electrolyte 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; the above values can use any listed point values, or can use the numerical range formed by any two point values.
[0045] In a further most preferred embodiment, the composition of the composite solid electrolyte membrane is as follows: the total weight of the composite solid electrolyte membrane is 100%, and the inorganic solid electrolyte accounts for 80% to 90% of the total weight; one or more of the binders account for 4% to 7% of the total weight; the inorganic skeleton material accounts for 0.5% to 1.2% of the total weight; the inorganic material additives account for 0.5% to 1.2% of the total weight; and the liquid electrolyte accounts for 3.5% to 8% of the total weight.
[0046] As a preferred embodiment, the total weight of the solid negative electrode is 100%, the negative electrode active material accounts for 85% to 97% of the total weight, the conductive carbon accounts for 0.5% to 1.5% of the total weight; the binder accounts for 0.5% to 3.5% of the total weight; the inorganic electrolyte accounts for 0.5% to 5% of the total weight; the liquid electrolyte accounts for 0.5% to 8% of the total weight; and the inorganic skeleton material accounts for 0.5% to 1.5% of the total weight.
[0047] As a preferred embodiment, the weight proportion of each component in the negative electrode membrane includes but is not limited to: active material 85%, 87%, 89%, 91%, 93%, 95%, 97%; conductive carbon 0.5%, 1.0%, 1.5%; binder 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%; inorganic electrolyte 0.5%, 1%, 2%, 3%, 4%, 5%; inorganic skeleton material 0.5%, 1.0%, 1.5%; the above values can use any listed point values, or can use the numerical range formed by any two point values.
[0048] In a further most preferred embodiment, the total weight of the solid negative electrode is 100%, the negative electrode active material accounts for 87% to 96% of the total weight, the conductive carbon accounts for 0.8% to 1.5% of the total weight; the binder accounts for 1% to 3.5% of the total weight; the inorganic electrolyte accounts for 1% to 5% of the total weight; the liquid electrolyte accounts for 1% to 8% of the total weight; and the inorganic skeleton material accounts for 0.8% to 1.5% of the total weight.
[0049] As a preferred embodiment, the total weight of the liquid electrolyte is 100%, the organic solvent accounts for 75% to 85%; the lithium salt accounts for 8% to 17%; and the electrolyte additive accounts for 0.5% to 10%.
[0050] As a preferred embodiment, the weight proportion of each component in the liquid electrolyte includes but is not limited to: organic solvent 75%, 77%, 79%, 81%, 83%, 85%; lithium salt 8%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%; electrolyte additives 0.5%, 1.5%, 2.5%, 3.5%, 4.5%, 5.5%, 6.5%, 7.5%, 8.5%, 9.5%, 10%.
[0051] In a further most preferred embodiment, the total weight of the liquid electrolyte is 100%, the organic solvent accounts for 80% to 85%; the lithium salt accounts for 10% to 15%; and the electrolyte additive accounts for 1% to 8%.
[0052] As a preferred embodiment, the composite solid electrolyte membrane further includes an inorganic material additive. The total weight of the solid electrolyte membrane is 100%, and the inorganic material additive accounts for 0.3% to 2%. In a further optimal embodiment, the inorganic material additive accounts for 0.5% to 1.5%.
[0053] As a preferred embodiment, the weight proportion of the inorganic material additive component in the composite solid electrolyte membrane includes but is not limited to: 0.3%, 0.8%, 1.3%, 1.8%, and 2%.
[0054] As a preferred embodiment, the thickness of the composite solid electrolyte membrane is 10 μm to 35 μm, and a further preferred thickness is 15 μm to 30 μm. In a preferred embodiment, the composite solid electrolyte membrane can also be composited with the surfaces of both sides of the solid positive and negative electrode membranes, and then laminated to produce a lithium-ion battery.
[0055] The present invention provides a method for preparing the composite solid electrolyte membrane and a solid lithium ion battery containing an inorganic skeleton material component. The preparation method mainly includes the following steps: (1) preparation of a solid electrode; (2) preparation of a composite solid electrolyte membrane; (3) assembly of a solid lithium ion battery.
[0056] The preparation process is as follows: (1) The solid positive electrode is prepared by mixing the positive electrode active material, conductive carbon, binder, and inorganic electrolyte uniformly, and then adding the liquid electrolyte to mix them thoroughly to make a block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine, and then bonded to the surfaces of both sides of the positive electrode current collector aluminum foil to obtain a solid positive electrode. (2) The composite solid electrolyte membrane is prepared by mixing the inorganic electrolyte, binder, and inorganic material additive uniformly, and then adding the inorganic skeleton material and liquid electrolyte to mix them thoroughly to make a block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine to obtain a composite solid electrolyte membrane. (3) The solid negative electrode is made by mixing and stirring the negative electrode active material, conductive carbon, binder, inorganic electrolyte, and inorganic skeleton material, and then adding the liquid electrolyte to mix them thoroughly to make a block granular material; then adding the liquid electrolyte to mix them thoroughly to make a block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine, and then bonded to the surfaces of both sides of the negative electrode current collector copper foil to obtain a solid negative electrode of inorganic skeleton material. (4) The solid positive electrode, composite electrolyte membrane, and solid negative electrode are cut, laminated, packaged, and hot-pressed in sequence to obtain the composite solid-state lithium-ion battery.
[0057] Preferably, in the implementation step (1), the positive electrode active material, conductive carbon, binder, and inorganic electrolyte are mixed in proportion, mixed at a low speed of 6 m / s, and then mixed at a high speed of 28 m / s to achieve binder fiberization; then a certain proportion of liquid electrolyte is added and mixed evenly to obtain millimeter-sized block particles; the block particles are put into a dry all-in-one machine to form a film at high temperature, and gradually thinned to obtain an electrode film; the electrode film is attached to both sides of a carbon-coated aluminum foil current collector to obtain a solid positive electrode. In step (2), the inorganic electrolyte, binder, additive, and inorganic skeleton material are mixed according to the formula ratio, mixed at a low speed of 6 m / s, and then mixed at a high speed of 22 m / s to achieve binder fiberization, and then the liquid electrolyte is added and mixed evenly to obtain millimeter-sized block particles; the block particles are put into a dry all-in-one machine and pressed at high temperature to form a film, and then thinned step by step to obtain a composite solid electrolyte membrane. In step (3), the negative electrode active material, conductive carbon, binder, inorganic electrolyte, and inorganic skeleton material are mixed in proportion, mixed at a low speed at a linear speed of 6 m / s, and then mixed at a high speed at a linear speed of 26 m / s to achieve binder fiberization, and then the liquid electrolyte is added and mixed evenly to obtain millimeter-scale block particles; the block particles are put into a dry all-in-one machine for film thinning to obtain an electrode film; the electrode film is attached to both sides of a carbon-coated copper foil current collector to obtain a solid negative electrode. Example 1
[0058] Step 1, positive electrode preparation: raw materials are prepared according to the weight ratio of lithium nickel cobalt manganese oxide (NCM811): conductive carbon black (SP): single-arm carbon nanotube (CNT): PTFE: lithium aluminum titanium phosphide (LiALTiP): liquid electrolyte = 87.15:1:0.05:1.8:5:5; the liquid electrolyte is 1M LiFSI dissolved in a solvent of EC:EMC=3:7, and then 0.5% MMDS and 0.5% LiPO4 are added to the liquid electrolyte. 2 F 2 ; First, NCM811, SP, CNT, and LiALTiP are mixed evenly, PTFE is added, and low-speed mixing is performed at a linear speed of 6 m / s. Then, high-speed mixing is performed at a linear speed of 28 m / s to achieve adhesive fiberization, and then liquid electrolyte is added and mixed evenly to obtain millimeter-scale block particles; the block particles are put into a dry-process integrated machine at medium pressure and high temperature to form a film, and gradually thinned to obtain a 45μm thick electrode film; the electrode film is bonded to both sides of a 10μm carbon-coated aluminum foil current collector to obtain a 100μm thick semi-solid positive electrode.
[0059] Step 2: Preparation of composite electrolyte membrane: Raw materials are prepared according to the weight ratio of LATP: PTFE: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polymethyl methacrylate (PMMA): inorganic skeleton material, inorganic material additive, liquid electrolyte = 85:1.5:4:1:1:0.5:7; the liquid electrolyte is 1M LiTFSI is dissolved in a solvent of EC:EMC:γ-butyrolactone (GBL):N,N-dimethylformamide (DMF) = 3:6:0.5:0.5, and 1% vinylene carbonate (VC), 1% 1,3-propane sultone (PS), and 5% fluoroethylene carbonate (FEC) are added to the total weight of the liquid electrolyte; LATP, PVDF-HFP, PMMA, and skeleton-free materials are first mixed evenly, PTFE is added, and mixed at a low speed of 6m / s, and then mixed at a high speed of 22m / s to achieve binder fiberization, and then the liquid electrolyte is added and mixed evenly to obtain millimeter-sized block particles; the block particles are put into a dry all-in-one device and pressed into a film at high temperature, and then thinned step by step to obtain a 20μm composite solid electrolyte membrane.
[0060] Step 3, negative electrode preparation: raw materials are prepared according to the weight ratio of silicon carbon material: SP: single-arm carbon nanotube (CNT): PTFE: lithium lanthanum zirconium tantalum oxide (LLZTO): liquid electrolyte: inorganic skeleton material = 90.15:0.8:0.05:1.5:2:4.5:1; the liquid electrolyte is 1M LiFSI is dissolved in a solvent with a ratio of EC:EMC=3:7, and then 5% FEC and 1% DTD of the liquid electrolyte are added; first, the silicon-carbon material, SP, CNT, LLZTO, and inorganic skeleton material are mixed evenly, and PTFE is added. After low-speed mixing at a linear speed of 6m / s, high-speed mixing is performed at a linear speed of 26m / s to achieve binder fiberization, and then the liquid electrolyte is added and mixed evenly to obtain millimeter-scale block particles; the block particles are put into a dry all-in-one machine for film thinning to obtain a 50μm electrode film; the electrode film is bonded to both sides of a 5μm carbon-coated copper foil current collector to obtain a semi-solid negative electrode with a thickness of 105μm.
[0061] Step 4, battery assembly: stack the completed positive electrode, solid electrolyte membrane, and negative electrode in order, and perform hot pressing of the aluminum-plastic film package of the outer shell. The temperature, pressure, and time of hot pressing are 92°C, 0.4MPa, and 130s, respectively, to obtain a soft-package composite solid-state lithium-ion battery. After the formation and capacity division processes, the performance test is performed and recorded in the table. Example 2
[0062] It is basically the same as Example 1, except that: Step 1: The thickness of the solid electrolyte membrane is 15 μm. Example 3
[0063] It is basically the same as Example 1, except that: Step 1: The thickness of the solid electrolyte membrane is 30 μm. Example 4
[0064] It is basically the same as Example 1, except that: Step 2: The active positive electrode material is lithium cobalt oxide, and the charging cut-off voltage is 4.53V.
[0065] It is basically the same as Example 1, except that: Step 1: No skeleton-free material is added to the ingredients.
[0066] It is basically the same as Example 1, except that: Step 1: No skeleton-free material is added to the ingredients.
[0067] The positive electrode is mixed evenly in NMP solvent with a weight ratio of NCM811:SP:CNT:PVDF=96.7:1:0.3:2 to prepare slurry, which is then coated, dried, and rolled to form a positive electrode sheet.
[0068] Negative electrode: Silicon carbon: SP: single-arm CNT: CMC: SBR = 96:1:0.01:1:2 are mixed evenly in a water solvent to prepare a slurry, which is then coated, dried, and rolled to form a negative electrode sheet.
[0069] Diaphragm: The diaphragm is made of 9μm PE base film plus 2μm aluminum oxide coating.
[0070] Electrolyte: 1M LiPF 6 Dissolved in EC:EMC=3:7 solvent, and added with 1% vinylene carbonate (VC), 1.5% 1,3-propane sultone (PS), 5% fluoroethylene carbonate (FEC), and 2% LiFSI to the total weight of the liquid electrolyte.
[0071] Battery assembly: The above positive electrode, separator, and negative electrode are stacked and assembled in sequence, and the electrolyte is injected and packaged to obtain a soft-pack battery. After formation and capacity division, the electrical performance test is carried out, which is also recorded in Table 1.
[0072] The specific test method is as follows: (positive electrode 811 cut-off voltage 4.2V, lithium cobalt oxide cut-off voltage 4.53V) (1) Room temperature cycle performance test: At 25°C, the formed battery is charged to 4.2V at 0.5C constant current and constant voltage (cut-off current is 0.01C), and then discharged to 3.0V at 0.5C constant current. The capacity retention rate after 500 cycles of charge / discharge is calculated as follows: Capacity retention rate after 500 cycles (%) = 500th cycle discharge capacity / 1st cycle discharge capacity × 100% (2) High temperature storage performance test: The thickness of the formed battery is tested. It is charged to 4.2V at 25°C using a constant current and constant voltage of 0.5C (cut-off current is 0.01C), and then stored at a high temperature of 85°C for 6 hours. After the high temperature storage, the thickness of the cell or battery is measured in an oven, and the increase rate of the battery thickness before and after the high temperature storage is calculated. The calculation formula is as follows: Battery thickness increase rate (%) = (battery thickness after high temperature - battery thickness before high temperature) / battery thickness before high temperature × 100% Thermal shock performance test: Charge to 4.2V at 0.5C constant current and constant voltage at 25℃ (cut-off current is 0.01C), put the cell or battery into the oven, and heat the oven to 150℃±2℃ at a rate of 5℃±2℃ / minute. When the oven reaches 150℃±2℃, keep it for 10 minutes. The battery passes the test if it does not catch fire or explode.
[0073] Needle puncture test: Room temperature cycle performance test: At 25°C, the formed battery is charged to 4.2V with 0.5C constant current and constant voltage (cut-off current is 0.01C), and then a 5mm steel needle is used to penetrate the battery cell at 25mm / s, and the battery status is recorded.
[0074] The test results are as follows (Table 1):
[0075] Table 1 Based on the test results of the embodiments and comparative examples in Table 1, it can be seen that the composite solid electrolyte based on the present invention can effectively solve the safety hazards of lithium-ion batteries. The solid-state batteries prepared in the embodiments perform well in thermal shock and needle puncture tests. The composite solid electrolyte membrane containing inorganic skeleton materials replaces conventional diaphragms, which can effectively improve the short circuit caused by thermal shrinkage of the diaphragm and the safety hazards caused by it. The high-temperature storage thickness change of the battery is significantly reduced, and the cycle life is extended.
[0076] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A composite solid-state lithium-ion battery, which is mainly divided into three parts: a solid positive electrode, a solid negative electrode containing a skeleton-free material, and a composite solid electrolyte membrane containing an inorganic skeleton material; That The characteristics are: The solid positive electrode comprises positive electrode active material, conductive carbon, binder, inorganic electrolyte and liquid electrolyte, the above materials are stirred and mixed, heated and pressed into a film by a dry process integrated machine, and composited with the surfaces of both sides of the positive electrode current collector aluminum foil to form a positive electrode; The composite solid electrolyte membrane comprises an inorganic electrolyte, a binder, an inorganic skeleton material, an inorganic material additive and a liquid electrolyte, and the mixture of the above materials is hot-pressed into a composite solid electrolyte membrane by a dry all-in-one machine; The solid negative electrode containing inorganic skeleton material components comprises negative electrode active material, conductive carbon, binder, inorganic electrolyte, liquid electrolyte and inorganic skeleton material. The above materials are stirred and mixed, heated and pressed into a film by a dry all-in-one machine, and then composited with the surfaces of both sides of the current collector copper foil to form the negative electrode.
2. The composite solid-state lithium-ion battery according to claim 1, Features: The composition ratio of the solid positive electrode is: The total weight of the solid positive electrode is 100%, the positive electrode active material accounts for 80% to 98% of the total weight; the conductive carbon accounts for 0.5% to 3.5% of the total weight; the binder accounts for 0.5% to 4.0% of the total weight; the inorganic electrolyte accounts for 0.5% to 8% of the total weight; the liquid electrolyte accounts for 0.5% to 8% of the total weight; The composition ratio of the composite solid electrolyte membrane containing inorganic skeleton material is: The total weight of the composite solid electrolyte membrane containing inorganic skeleton materials is 100%, wherein the inorganic solid electrolyte accounts for 74% to 95% of the total weight; the binder accounts for 3% to 8% of the total weight; the inorganic skeleton material accounts for 0.5% to 1.5% of the total weight; the additive accounts for 0.5% to 1.5% of the total weight; and the liquid electrolyte accounts for 3% to 10% of the total weight; The composition ratio of the solid negative electrode containing the framework-free material is: The total weight of the solid negative electrode containing the framework-free material is 100%, the negative electrode active material accounts for 85% to 97% of the total weight, the conductive carbon accounts for 0.5% to 1.5% of the total weight; the adhesive accounts for 0.5% to 3.5% of the total weight; the inorganic electrolyte accounts for 0.5% to 5% of the total weight; the liquid electrolyte accounts for 0.5% to 8% of the total weight; and the inorganic framework material accounts for 0.5% to 1.5% of the total weight.
3. The composite solid-state lithium-ion battery according to claim 2, Features: The positive electrode active material includes at least one of a nickel-cobalt-manganese ternary positive electrode material, a nickel-cobalt-aluminum ternary positive electrode material, a lithium iron phosphate positive electrode material, a lithium manganate positive electrode material, a lithium cobaltate positive electrode material, a lithium iron phosphate manganese positive electrode material, a lithium nickel manganate positive electrode material or a lithium-rich manganese-based positive electrode material; the negative electrode active material is a composite negative electrode material of silicon carbon or silicon dioxide and artificial graphite.
4. The composite solid-state lithium-ion battery according to claim 2, It is characterized in that The inorganic electrolyte material is at least one of the following materials: lithium germanium phosphosulfide, lithium phosphosulfur halide, lithium aluminum phosphide, lithium aluminum titanium phosphide, lithium lanthanum zirconium oxide, lithium phosphosulfide, lithium lanthanum zirconium tantalum oxide.
5. The composite solid-state lithium-ion battery according to claim 2, It is characterized in that The binder in the solid positive electrode and / or the solid negative electrode containing the framework-free material includes at least one of polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid or polyethylene.
6. The composite solid-state lithium-ion battery according to claim 2, It is characterized in that The inorganic framework material in the composite solid electrolyte membrane containing inorganic framework material and the solid negative electrode containing framework-free material is sodium lithium silicate; As one of the components of the composite solid electrolyte membrane and the solid negative electrode, the inorganic skeleton material is heated and pressed by a dry all-in-one machine during the production of the composite solid electrolyte membrane and the solid negative electrode to form an inorganic support skeleton network in the composite solid electrolyte membrane and the negative electrode.
7. The composite solid-state lithium-ion battery according to claim 2, It is characterized in that The liquid electrolyte contains an organic solvent, a lithium salt, and an electrolyte additive; The organic solvent has the function of dissolving the lithium salt and also has the function of a plasticizer. The organic solvent includes a mixture of two or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, γ-butyrolactone, and N,N-dimethylformamide; Also included are fluorinated solvents selected from the group consisting of 2,2,2-trifluoroethyl methyl carbonate, 2,2,2-trifluorodiethyl carbonate, and 2,2,2-trifluoroethylpropyl carbonate, or a mixture of more than one thereof; The total weight of the liquid electrolyte is 100%, and the organic solvent accounts for 75% to 85%; The lithium salt is mainly lithium bis(trifluoromethylsulfonyl imide), and also includes a mixture of one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluorooxalatophosphate, lithium bis(fluorosulfonyl imide), lithium difluorobis(malonate phosphate) and lithium hexafluorophosphate; The total weight of the liquid electrolyte is 100%, and the lithium salt accounts for 8% to 17%; The electrolyte additives also include vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propylene sultone, 1,4-butane sultone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethylene glycol dipropionitrile ether, tris(2,2,2-trifluoroethyl)phosphite, 1,3,6-hexanetrinitrile, citric anhydride, perfluoroglutaric anhydride, fluorobenzene, 2-fluorobiphenyl, boron trifluoride tetrahydrofuran, tris(trimethylsilane) phosphate, cyclic phosphoric anhydride, vinyl sulfate, perfluorobenzene, olefinic polyfluorobenzene, perfluorobenzene, olefinic polyfluorobenzene, one or more thereof; The total weight of the liquid electrolyte is 100%, and the electrolyte additive accounts for 0.5% to 10%.
8. The composite solid-state lithium-ion battery according to claim 2, Features: The composite solid electrolyte membrane also includes inorganic material additives. The inorganic particles interact with the electrolyte interface and can also provide a higher conductivity of the electrolyte. The addition of inorganic fillers can also increase the mechanical strength of the electrolyte and improve the usability of the solid electrolyte membrane. The inorganic material additive includes aluminum oxide, boehmite, and lithium silicate; The total weight of the solid electrolyte membrane is 100%, and the inorganic material additive accounts for 0.3% to 2%.
9. A method for preparing a composite solid-state lithium-ion battery as claimed in claims 1 to 8, It is characterized in that The following steps are involved: Preparation of solid positive electrode: The solid positive electrode is prepared by mixing positive electrode active material, conductive carbon, binder and inorganic electrolyte evenly, and then adding liquid electrolyte to mix them thoroughly to form block particles; the block particles are heated and pressed into a film by a dry all-in-one machine, and then compounded with the surfaces of both sides of the positive electrode current collector aluminum foil to obtain a solid positive electrode; Preparation of composite solid electrolyte membrane containing inorganic skeleton material: the composite solid electrolyte membrane is prepared by mixing and stirring the inorganic electrolyte, the binder and the additive, and then adding the inorganic skeleton material and the liquid electrolyte to mix them fully to form a block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine to obtain a composite solid electrolyte membrane; Preparation of a solid negative electrode containing an inorganic skeleton material: The solid negative electrode is prepared by mixing and stirring a negative electrode active material, conductive carbon, a binder, and an inorganic electrolyte, and then adding an inorganic skeleton material and a liquid electrolyte to mix them thoroughly to make a block granular material; then adding an inorganic skeleton material and a liquid electrolyte to mix them thoroughly to make a block granular material; the block granular material is heated and pressed into a film by a dry all-in-one machine, and then compounded with the surfaces of both sides of the negative electrode current collector copper foil to obtain a solid negative electrode of an inorganic skeleton material; The solid positive electrode, the composite solid electrolyte membrane containing inorganic skeleton materials, and the solid negative electrode containing inorganic skeleton materials are cut, stacked, packaged and hot-pressed in sequence to obtain the composite solid-state lithium-ion battery.
